Diagnostic potential of peri‐implant crevicular fluid microRNA‐21‐3p and microRNA‐150‐5p and extracellular vesicles in peri‐implant diseases. Issue 6 (13th November 2020) - Chaparro, Alejandra; Atria, Pablo; Realini, Ornella; Monteiro, Lara J.; Betancur, Daniel; Acuña‐Gallardo, Stephanie; Ramírez, Valeria; Bendek, María José; Pascual, Andrés; Nart, José; Beltrán, Victor; Sanz, Antonio
Abstract: Background: To explore the diagnostic usefulness of extracellular vesicles (EVs), and their subpopulations (micro‐vesicles and exosomes), and microRNAs (miRNA‐21‐3p, miRNA‐150‐5p, and miRNA‐26a‐5p) in peri‐implant crevicular fluid (PICF) of subjects with healthy, peri‐implant mucositis and peri‐implantitis implants. Methods: A total of 54 patients were enrolled into healthy, peri‐implant mucositis, and peri‐implantitis groups. PICF samples were collected, EVs subpopulations (MVs and Exo) were isolated and characterized by nanoparticle tracking analysis and transmission electron microscopy. The expression of miRNA‐21‐3p, miRNA‐150‐5p and miRNA‐26a‐5p was quantified by qRT‐PCR. Logistic regression models and accuracy performance tests were estimated. Results: PICF samples show the presence of EVs delimited by a bi‐layered membrane, in accordance with the morphology and size (< 200 nm). The concentration of PICF‐EVs, micro‐vesicles and exosomes was significantly increased in peri‐implantitis implants compared to healthy implants ( P = 0.023, P = 0.002, P = 0.036, respectively). miRNA‐21‐3p and miRNA‐150‐5p expression were significantly downregulated in patients with peri‐implantitis in comparison with peri‐implant mucositis sites ( P = 0.011, P = 0.020, respectively ). The reduced expression of miRNA‐21‐3p and miRNA‐150‐5p was associated with peri‐implantitis diagnosis (OR:0.23, CI 0.08‐0.66, P = 0.007 and OR:0.07, CI 0.01‐0.78, P = 0.031, respectively). The model which included the miRNA‐21‐3p and miRNA‐150‐5p expression had a sensitivity of 93.3%, a specificity of 76.5%, a positive predictive value of 77.8%, and a negative predictive value of 92.9%. The positive and negative likelihood ratios were 3.97 and 0.09, respectively. The area under the receiver operating characteristics curve for the model was 0.84. Conclusions: An increase concentration of EVs with a downregulation expression of miRNA‐21‐3p and miRNA‐150‐5p could be related with the peri‐implantitis development.